Ecological Harmony in the Perspective of the Qur'an: Ecological Piety as a Solution to the Disaster of Deforestation - Muhammad Yusril Kurniawan; Ikmal Maulana; Zainudin; Abdul Qudus (CV. Abhinaya Indo Group, 2025)
Deforestation in Indonesia has reached a critical stage and caused a series of ecological disasters, including flash floods on the island of Sumatra that claimed many lives. This study aims to analyse the concept of ecological harmony from the perspective of the Qur'an and formulate principles of ecological piety as a mitigative solution to the deforestation crisis. The method used is qualitative with a descriptive-analytical approach through library research, reinforced by socio-ecological analysis to connect the interpretation of verses with the reality of environmental damage. Primary data was obtained from a direct study of Tafsir al-Azhar by Hamka and Tafsir al-Misbah by Quraish Shihab, while secondary data was obtained from scientific literature related to ecological crises, deforestation, and ecological verses. The results of the study show that the Qur'an, through QS. Ar-Rum: 41, directly links ecological damage to human actions, while QS. Ar-Rahman: 7–9 emphasises the principle of mizan (balance) as a fundamental structure of nature that must be preserved by humans as caliphs. The interpretation of the scholars describes that hypocrisy does not only mean moral corruption, but also includes tangible ecological damage such as pollution, forest degradation, and climate change. Based on these findings, the study formulated six principles of ecological piety: respect for nature, moral responsibility, cosmic solidarity, ecological compassion, ecological justice, and ecological restoration as an ethical framework relevant to responding to the environmental crisis.